The Influence of Safety Leadership Through Safety Behaviour on Work Accident in Can Department of PT. XYZ - Faradico, Ariesto Christopher; Sary, Fetty Poerwita (Asian Journal of Management Analytics, 2024)
PT. XYZ has a worrying rate of work accidents in the canning department. This is not in accordance with the company's target of "Zero Accident". This finding further shows that safety leadership and safety behaviour in the can department need to be analyzed more deeply. The purpose of this study is to find out the application of safety leadership in the can department of PT. XYZ, knowing the implementation of safety behaviour in the can department of PT. XYZ, knowing about the work accident in the can department of PT. XYZ, knowing the influence of safety leadership on work accidents in the can department of PT. XYZ, knowing the influence of safety behaviour on work accidents in the can department of PT. XYZ, and knowing the influence of safety leadership through safety behavior on work accidents in the can department of PT. XYZ. The method used in the study is quantitative research with the data source being the operators of the can department whose data is collected through a questionnaire. The data obtained will be processed using SEM-PLS. The results of this study found that safety leadership had a significant influence on work accidents with a t-value of 2,233; Safety leadership has a significant influence on safety behavior with a t-value of 2.714; safety behaviour had a significant influence on work accidents with a t-value of 2.112; and safety leadership through safety behavior has a significant influence on work accidents with a t-value of 2.277.